Correlation of Clinical and Histopathological Diagnosis of Oral Mucosa Lesions at the University of Costa Rica Between 2008 and 2015 - Boza Oreamuno, Yadira V. (2020)
The objective of this study is to determine the existing concordance between the clinical and histopathological diagnosis of lesions in the oral mucosa at the Faculty of Dentistry of the University of Costa Rica (UCR). A retrospective study of 261 reports of oral lesions recovered from the biopsy archive of the UCR Faculty of Dentistry from 2008 to 2015. Of the total reports 165 were included in the analysis, 96 (36.8%) did not have any diagnostic hypotheses. The concordance between the clinical and histopathological diagnosis was verified by the Kappa test. Concordance with the first diagnostic hypothesis was presented in 114 (69.1%) cases, the value of kappa was 0.663 (substantial agreement) and 36.8% without clinical diagnosis only a description of the lesion.  The premalignant lesions presented an excellent concordance (kappa=0.902). The concordance of the group of non-neoplastic proliferative lesions was moderate (kappa=0.504) and the dermatological and autoimmune conditions with negligible concordance (0.157). Concordance occurred in the majority of the patients investigated with a value corresponding to a substantial agreement, however, the percentage of reports that did not have a clinical hypothesis should be improved.